Direct Synthesis of Aluminosilicate SSZ-39 Zeolite Using Colloidal Silica as a Starting Source - Xu, Hao; Zhang, Juan; Wu, Qinming; Chen, Wei; Lei, Chi; Zhu, Qiuyan; Han, Shichao; Fei, Jinhua; Zheng, Anmin; Zhu, Longfeng; Meng, Xiangju; Maurer, Stefan; et al. (ACS applied materials & interfaces, 2019)
For the first time, SSZ-39 zeolite has been directly prepared using conventional colloidal silica and sodium aluminate instead of using FAU zeolite as the raw material in the alkaline media. The adjustment of the Si/Al ratios in the starting materials to the suitable values is a key factor to prepare the aluminosilicate SSZ-39 zeolite. Various characterizations (for instance, X-ray diffraction, scanning electron microscopy, nitrogen sorption, solid Al NMR, and NH -temperature-programmed desorption) display that the aluminosilicate SSZ-39 zeolite owns high crystallinity, uniform cuboid morphology, large surface area, four-coordinated aluminum species, and strong acidic sites. Inductively coupled plasma analysis shows that the SiO /Al O ratios of the SSZ-39 products are ranged from 12.8 to 16.8. Considering the special framework of the SSZ-39 zeolite, the yield of this synthesis is not higher than 21.3%. Moreover, the catalytic performance of Cu-SSZ-39 catalyst synthesized from this route is excellent in the selective catalytic reduction of NO with NH (NH -SCR).